Collateral damage of COVID-19: late presentation of cerebrovascular accident - Ismail, Hazwani; Wan Zul Haikal Hafiz; Md Pauzi, Ahmad Luqman; Chao, Loh Wei; Yin, Lau Su (Malaysian Medical Association, 2023)
Coronavirus disease 2019 (COVID-19) is associated with an increased risk of death due to the sequelae of inflammation and thrombosis. Patients infected with COVID-19 are at risk of ischemic stroke due to the effects of inflammatory cytokine storm, platelet activation, endothelial dysfunction and prolonged stasis. We report a case of severe COVID-19 infection who developed acute ischemic stroke during the course of his illness. The patient did not carry any traditional risk of stroke or thromboembolic event and was vaccinated. He tested positive for COVID-19 infection, but due to respiratory distress, he was intubated and ventilated. On the 11th day in intensive care unit, he was noted to be hemiplegic with poor neurological recovery. Despite being on treatment dose enoxaparin, his computed tomography confirmed a lacunar infarct in his brain and bilateral pulmonary embolisms. Twenty-five days later, he remained well and was discharged home with dabigatran and atorvastatin.